Personality Style, Kecemasan, dan Antenatal Care terhadap Risiko Stunting pada Bayi Ibu Remaja - Erlina Fauziah; Resti Dona Saputri; Israfil Israfil (Yayasan Jompa Research and Development, 2026)
Stunting remains a public health problem, especially in coastal areas. The stunting rate reached 29.5%, exceeding the national average of 21.6%. Teenage mothers are the most vulnerable group in the pregnancy and parenting cycle, not only due to biological factors but also due to psychosocial aspects such as high anxiety and low involvement in antenatal care (ANC) services. This study aims to analyze the influence of personality style, pregnancy anxiety, and ANC involvement on the risk of stunting in infants of teenage mothers in coastal areas. The study used a mixed methods sequential explanatory design. The quantitative phase involved 158 teenage mothers with stratified sampling, using instruments consisting of questionnaires on personality style, pregnancy anxiety, and antenatal care involvement that had been validated by three experts (Aiken's V = 0.86–0.94; α = 0.77–0.88; ω = 0.79–0.91). The analysis was conducted with Jamovi 2.6.44 using binary logistic regression and mediation analysis. The qualitative phase involved 12 informants, analyzed manually with six systematic stages of semi-structured protocol-based thematic analysis based on quantitative results. The results showed that maternal personality style had a significant influence in reducing the risk of stunting (OR = 0.17; p = 0.008), while anxiety and ANC were not significant individually, but together contributed significantly in the combined regression model (χ² (3) = 8.33; p = 0.040). Qualitative data confirmed that mothers with adaptive personalities tended to be better able to manage anxiety and utilize ANC consistently. Psychological factors in reducing the risk of stunting were more effective than single medical interventions.